Pneumocephalus after surgical treatment of NOE fracture: Case report (Research, Society and Development, 2022)
Introduction: Naso-orbital-ethmoidal fractures are complex fractures involving the bones of the nose, orbit region, maxilla and ethmoid. This complex structure has a close relationship with the brain and the orbital region, which frequently suffer injuries during trauma. Among traumatic brain injuries, there is the pneumoencephalon. The present study aims to report the treatment of a patient who suffered an accident involving a rural animal. Case Report: A 63-year-old male patient was brought to the highly complex hospital for the Oral and Maxillofacial Surgery and Traumatology service, five days after the trauma. The physical examination showed traumatic telecanthus,anisocoria and mydriasis of the right eye, right eyelid ptosis, laceration in the right eyebrow and deviation of the nasal bone to the left. In the imaging exam (computed tomography), traces of fractures were observed in the nasal bone region, medial orbital wall, infra-orbital margin, frontal-zygomatic pillar and right orbital blow out fracture. After a surgical approach to fix the fractures, it was observed the development of a hypodense area in the intracranial region, suggestive of pneumocephalus. Conclusion: These complications, such as pneumocephalus, must be diagnosed early and appropriate treatment must be started as soon as possible to reduce possible sequelae, requiring the intervention of a multidisciplinary team.